Signifying pain : constructing and healing the self through writing - Harris, Judith, 1955- (Albany : State University of New York Press, 2003)
"Signifying Pain applies the principles of therapeutic writing to such painful life experiences as mental illness, suicide, racism, domestic abuse, and even genocide. Probing deep into the bedrock of literary imagination, Judith Harris traces the odyssey of a diverse group of writers - John Keats, Derek Walcott, Jane Kenyon, Michael S. Harper, Robert Lowell, and Ai, as well as student writers - who have used their writing to work through and past such personal traumas. Drawing on her own experience as a poet and teacher, Harris shows how the process can be long and arduous, but that when exercised within the spirit of one's own personal compassion, the results can be limitless. Signifying Pain will be of interest not only to teachers of creative and therapeutic writing, but also to those with a critical interest in autobiographical or confessional writing more generally."--Jacket
Machine generated contents note: pt. I Speaking Pain: Women, Psychoanalysis, and Writing -- Ch. 1 Healing Effects of Writing about Pain: Literature and Psychoanalysis -- Ch. 2 Violating the Sanctuary/Asylum: Freudian Treatment of Hysteria in "Dora" and "The Yellow Wallpaper" -- Ch. 3 Breaking the Code of Silence: Ideology and Women's Confessional Poetry -- Ch. 4 Fathering Daughters: Oedipal Rage and Aggression in Women's Writing -- pt. II Soul-making: Conflict and the Construction of Identity -- Ch. 5 Carving the Mask of Language: Self and Otherness in Dramatic Monologues -- Ch. 6 Giotto's Invisible Sheep: Lacanian Mirroring and Modeling in Walcott's Another Life -- Ch. 7 Rescuing Psyche: Keats's Containment of the Beloved but Fading Woman in the "Ode to Psyche" -- Ch. 8 God Don't Like Ugly: Michael S. Harper's Soul-Making Music -- Ch. 9 Kenyon's Melancholic Vision in "Let Evening Come" -- pt. III Healing Pain: Acts of Therapeutic Writing -- Ch. 10 Using the Psychoanalytic Process in Creative Writing Classes -- Ch. 11 Rewriting the Subject: Psychoanalytic Approaches to Creative Writing and Composition Pedagogy -- Ch. 12 "To Bedlam and Almost All the Way Back": The Image and Function of the Institution in Confessional Poetry -- Ch. 13 Asylum: As Personal Essay -- Ch. 14 Signifying Pain: Recovery and Beyond.
Includes bibliographical references (pages 259-289) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Creative writing -- Therapeutic use -- Congresses; Psychoanalytic interpretation; Self-perception.; Writing; Psychoanalytic Interpretation; Literature; Self Concept; Stress, Psychological -- psychology; Writing; Création littéraire -- Emploi en thérapeutique -- Congrès.; Interprétation psychanalytique; Littérature.; Perception de soi; Écriture.; writing (processes); MEDICAL -- Allied Health Services -- Occupational Therapy; Writing; Self-perception; Psychoanalytic interpretation; Creative writing -- Therapeutic use; Conference papers and proceedings